2010
DOI: 10.1002/tea.20378
|View full text |Cite
|
Sign up to set email alerts
|

Students' comprehension of science textbooks using a question‐based reading strategy

Abstract: Despite the heavy reliance on textbooks in college courses, research indicates that college students enrolled in first-year science courses are not proficient at comprehending informational text. The present study investigated a reading comprehension questioning strategy with origins in clinical research based in elaboration interrogation theory, which outlines how to encourage readers to recall relevant background knowledge while reading text materials. The theory suggests that the strategy increases the like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…Research shows that providing questions for the meaning of a text can encourage learners to activate their relevant prior knowledge and to integrate it with the text content. This additional cognitive activity can deepen comprehension of the text and generate responses more elaborative than verbatim recitation of the text would (Seifert 1993;Graesser, Baggett, and Williams 1996;Callender and McDaniel 2007;Smith, Holliday, and Austin 2010). The effects of providing adjunct questions also include improvements in (1) memory of factual knowledge, (2) inferential knowledge and (3) grasp of a text's main ideas (Woloshyn, Pressley, and Schneider 1992;Seifert 1993;Pressley and McCormick 1995).…”
Section: Question-based Instructionmentioning
confidence: 92%
See 1 more Smart Citation
“…Research shows that providing questions for the meaning of a text can encourage learners to activate their relevant prior knowledge and to integrate it with the text content. This additional cognitive activity can deepen comprehension of the text and generate responses more elaborative than verbatim recitation of the text would (Seifert 1993;Graesser, Baggett, and Williams 1996;Callender and McDaniel 2007;Smith, Holliday, and Austin 2010). The effects of providing adjunct questions also include improvements in (1) memory of factual knowledge, (2) inferential knowledge and (3) grasp of a text's main ideas (Woloshyn, Pressley, and Schneider 1992;Seifert 1993;Pressley and McCormick 1995).…”
Section: Question-based Instructionmentioning
confidence: 92%
“…In addition, because people learn everyday concepts and academic-oriented unique concepts in different contexts and according to different methods, the differences among concept mappings that correspond to different types of concepts could manifest themselves much as concept-mapping associates with different motivational factors and cognitive strategies. Thus, it is hypothesised that different motivation factors and different cognitive strategies can help predict concept-mapping performances for concepts involving different knowledge prototypes Second, many studies have shown that adjunct questions help students integrate prior knowledge into current reading materials, so as to improve students' comprehension of and recall of the reading materials' content (Bing 1982;Smith, Holliday, and Austin 2010). Because applying the 6W scaffold to concept mapping is expected to help students explore the multidimensionality characterising each concept node, it is hypothesised that students who use the 6W scaffold can retrieve more nodes, create more propositions and do so more productively than is the case with students who do not use the scaffold.…”
Section: Hypothesesmentioning
confidence: 99%
“…• 'The odd question': The brain generates dopamine (thus guaranteeing learning) in front of the unexpected [29]. Examples such as 'Why is it successful, from an evolutionary perspective, privileging a single organ, thus preventing life in case of damage?'…”
Section: Neuroscience In the Classroommentioning
confidence: 99%
“…There is less exploration of the integration of reading comprehension instruction as part of discipline-specific content courses intended for first-year students (for an exception see Shepherd, Selden, & Selden's, 2009 research exploring reading instruction as part of first-year mathematics). Even when such studies exist, they are often limited to the use of a specific comprehension strategy versus promoting an extensive repertoire.…”
Section: Reading Comprehension and Strategy Instructionmentioning
confidence: 99%